Analysis of the Quality of First Public Services Specifically in the Health Sector at the Bungamas Village Health Center, East Kikim District, Lahat Regency, South Sumatra Province, Indonesia: Analisis Kualitas Pelayanan Publik Pertama Khusus Di Bidang Kesehatan Pada Puskesmas Desa Bungamas Kecamatan Kikim Timur Kabupaten Lahat Provinsi Sumatra Selatan Indonesia - Khairunisa, Ellva; Ayustia, Risa (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to evaluate the quality of public services. And identify and analyze public perceptions of service quality at the Bunga Mas Village Health Center, Kikim Timur District, Lahat Regency, and South Sumatra Province. This study identified three main factors that influence service quality, namely the availability of medical personnel, facilities and infrastructure, and waiting time. The method used in this study is qualitative with a case study approach. At the same time, data collection includes in-depth interviews with the head of the health center, medical personnel, and community users of the service and patient satisfaction surveys. The data analysis technique used is descriptive analysis to describe the factors that influence service quality and public perception of service quality. The results of the study indicate that the availability of medical personnel is the main factor in providing patient satisfaction, while facility infrastructure and waiting time are still problems that need to be fixed. The conclusion of this study emphasizes the importance of increasing the number of medical personnel and improving facilities to improve the quality of health services. Suggestions are given to the management of the Health Center to pay attention to the need for facilities and infrastructure and optimize queue management to reduce patient waiting time.